Technology and employment in industry : (International Labour Office, 1975)
This book introduce issuses of concept and measurement, empirical case studies, prceding examination of some of the conceptual and measurement issuses relevant to the problem of technological choice, represents a contribution to the economics of technological possibilities open to developing countries.